Democratic Republic of the Congo : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2006)
The Congolese authorities requested an IMF staff-monitored program (SMP), in support of the economic program they spelled out in the accompanying Memorandum on Economic and Financial Policies (MEFP). The Democratic Republic of the Congo showed remarkable macroeconomic stability under the Poverty Reduction Growth Facility Program. The SMP is intended to preserve macroeconomic stability during the protracted elections and give the authorities an opportunity to establish a strong track record of policy implementation. The SMP includes measures for improving public resource management and strengthening central bank operations.